A comparative electrical conductivity behavior of BaTiO3 and CaTiO3 ceramics - Hapani D.S.; Singh P.; Jha P.K.; Singh P. (My University, 2025)
The conductivity in electrolyte materials for Solid Oxide Fuel Cells (SOFCs) was mainly attributed to the oxideions conductivity that originate from highly mobile oxygen ions. The dense grain growth and high oxide ion conductivity are the primary requisite properties for the electrolyte materials. To optimize the ionic conduction and grain growth, BaTiO3 and CaTiO3 were studied. The samples were synthesized by solid state reaction route. The structural studies were employed using XRD and suggest single phase formation of the compounds. The microstructural studies reveal the formation of dense grains. The high oxide-ion conductivity was obtained for the studied specimens. © 2018 Author(s).